2014
DOI: 10.1053/j.ajkd.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss, Adipokines, and Quality of Life After Sleeve Gastrectomy in Obese Patients With Stages 3-4 CKD: A Randomized Controlled Pilot Study

Abstract: A 61-year-old woman was admitted to our hospital with general fatigue. Laboratory tests showed kidney failure, and imaging showed visceral inversion with polycystic liver and kidneys (Fig 1). Autosomal dominant polycystic kidney disease (ADPKD) with complete situs inversus was diagnosed. Polycystins 1 and 2, proteins encoded by the PKD1 and PKD2 genes, respectively, are known to localize to renal tubular primary cilia. In addition, experiments in mice have shown that polycystin 2 has a role in left-right deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…8,12,14 One study of 13 patients with CKD who underwent bariatric surgery found that indexed mGFR and eGFR increased, leptin and adiponectin levels normalized, and C-reactive protein decreased 12 months after surgery. 12 Inflammation and dysregulated adipocytokines have both been postulated to have adverse effects on kidney.…”
Section: Discussionmentioning
confidence: 99%
“…8,12,14 One study of 13 patients with CKD who underwent bariatric surgery found that indexed mGFR and eGFR increased, leptin and adiponectin levels normalized, and C-reactive protein decreased 12 months after surgery. 12 Inflammation and dysregulated adipocytokines have both been postulated to have adverse effects on kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In a study led by Navaneethan etĀ al. , 13 patients with serum creatinine ā‰„Ā 1.3 mg/dl underwent measurement of GFR using iothalamate clearance before surgery and 3, 6, and 12 months after bariatric surgery (RYGB, 7; LAGB, 3; LSG,Ā 3) 47 . In contrast to the studies in patients with preserved GFR, unindexed mGFR in this CKD cohort remained unchanged at 12 months (82.0āˆ’80.5 ml/min, P Ā = 0.3).…”
Section: Overview Of Bariatric Surgery Typesmentioning
confidence: 99%
“…Baseline kidney disease included glomerular hyperfiltration [13][14][15]19], overt CKD [16][17][18][19][20][21][22][23][24], or end-stage renal disease [16]. There are two studies [16,20] including patients on hemodialysis (HD) treatment.…”
Section: Studies On Bariatric Surgery Included Collectively 773mentioning
confidence: 99%
“…The type of surgery performed in these studies is heterogeneous. 4 studies considered Roux-en-Y gastric bypass [15][16][17]23], and 2 studies [20,24] performed sleeve gastrectomy, in which MacLaughlin et al [20] used laparoscopic sleeve gastrectomy, to achieve weight loss. In the study by Hou et al [19], of 233 total patients, 184 patients underwent gastric bypass, 32 patients had sleeve gastrectomy and gastric banding was performed for 14 remaining patients.…”
Section: Studies On Bariatric Surgery Included Collectively 773mentioning
confidence: 99%